Expression of transglutaminase 2 in human gut epithelial cells: Implications for coeliac disease - Sunniva F. Amundsen; Jorunn Stamnaes; Knut E. A. Lundin; Ludvig M. Sollid (PLoS ONE, 2023)
Background Formation of complexes between transglutaminase 2 (TG2) and gluten can mechanistically explain why TG2 serves both as B-cell autoantigen and as an enzyme that creates deamidated gluten epitopes in coeliac disease (CeD). A model has been proposed where TG2 released from shed epithelial cells encounters high concentrations of dietary gluten peptides to form these TG2:gluten complexes. In this work we have characterised TG2 protein expression in gut epithelial cells in humans. Methods Western blot analysis, immunofluorescence staining and mass spectrometry in combination with laser capture microdissection to gain spatial resolution were used to characterise TG2 expression in the epithelial cell layer of healthy and coeliac disease affected duodenum. Findings TG2 is expressed in human duodenal epithelial cells, including cells in the apical region that are shed into the gut lumen. In untreated CeD the apical expression of TG2 is doubled. Enzymatically active TG2 is readily released from isolated human intestinal epithelial cells. Conclusion Shed epithelial cells are a plausible source of pathogenic TG2 enzyme in CeD. Increased epithelial TG2 expression and increased epithelial shedding in active CeD may reinforce action of luminal TG2 in this condition.